Groundnut shell carbon quantum dot magnetic iron oxide nanocomposite (GSCQD-FeFe2O4) for lead removal from water - Fredrick Saah; Garima Nagpal; Flomo Gbawoquiyq; Rashi Chaudhary (Zaštita Materijala)
A novel adsorbent, GSCQD-FeFe2O4, combining groundnut shell-derived carbon quantum dots with magnetic iron oxide nanoparticles, was synthesized for efficient removal of Pb(II) from water. Characterization studies confirmed successful synthesis, with UV analysis showing absorption at 210 nm and green luminescence indicating carbon quantum dots. FT-IR identified characteristic functional groups, while XRD confirmed well-ordered structures. FE-SEM revealed clustered carbon nanoparticles with magnetic iron oxide, and TEM showed small-sized carbon dots suitable for adsorption. Batch adsorption studies revealed optimal conditions for Pb(II) removal, including a pH range of 5-6, temperature of 20°C, contact time of 20 minutes, and adsorbent dose of 0.2 g. Isotherm studies indicated that both Langmuir and Freundlich models provided a good fit, with a calculated adsorption capacity of 37.8 mg/g. Thermodynamic analysis suggested spontaneous, exothermic adsorption with increased disorder. GSCQD-FeFe2O4 displayed excellent potential for Pb(II) removal, but further research on reusability and stability in industrial settings is needed for broader applicability.